Crystal structure of an RNA octamer duplex r(CCCIUGGG)2 incorporating tandem I.U wobbles. - Pan, B (1998)
The crystal structure of the RNA octamer duplex r(CCCIUGGG)2has been elucidated at 2.5 A resolution. The crystals belong to the space group P21and have unit cell constants a = 33.44 A, b = 43.41 A, c = 49.39 A and beta = 104.7 degrees with three independent duplexes (duplexes 1-3) in the asymmetric unit. The structure was solved by the molecular replacement method and refined to an Rwork/Rfree of 0.185/0.243 using 3765 reflections between 8.0 and 2.5 A. This is the first report of an RNA crystal structure incorporating I.U wobbles and three molecules in the asymmetric unit. Duplex 1 displays a kink of 24 degrees between the mismatch sites, while duplexes 2 and 3 have two kinks each of 19 degrees and 27 degrees, and 24 degrees and 29 degrees, respectively, on either side of the tandem mismatches. At the I.U/U.I mismatch steps, duplex 1 has a twist angle of 33.9 degrees, close to the average for all base pair steps, but duplexes 2 and 3 are underwound, with twist angles of 24.4 degrees and 26.5 degrees, respectively. The tandem I.U wobbles show intrastrand purine-pyrimidine stacking but exhibit interstrand purine-purine stacking with the flanking C.G pairs. The three independent duplexes are stacked non-coaxially in a head-to-tail fashion to form infinite pseudo-continuous helical columns which form intercolumn hydrogen bonding interactions through the 2'-hydroxyl groups where the minor grooves come together.